ANALISIS STANDARISASI MANAJEMEN PENERIMAAN PESERTA DIDIK DI SEKOLAH DASAR FUTUHIYAH SUKODONO SIDOARJO - Alif Bachtiar Usuludin; Slamet Widodo (LPPM Universitas Bina Bangsa, 2023)
Every school has a new student admission system. However, in fact not all schools are able to accept quite a lot of new students, especially schools that have just been established. This study aims to evaluate the management of new student admissions at the Futuhiyah Sukodono Elementary School, Sidoarjo, East Java. The research method is a qualitative descriptive case study approach. Collecting data using interview and observation techniques. The conclusions of this study are: the management of new student admissions at the Futuhiyah Sukodono Elementary School, Sidoarjo, East Java, is in accordance with the standards set in the aspects of planning new student admissions, organizing new student admissions, implementing new student admissions according to standards, and reporting new student admissions, while for monitoring and evaluation of new student admissions is not up to standard